Altered branched chain amino acid metabolism: toward a unifying cardiometabolic hypothesis. (September 2018) - Tobias, Deirdre K.; Mora, Samia; Verma, Subodh; Lawler, Patrick R.
Abstract : Purpose of review: Atherosclerotic cardiovascular disease (CVD) and type II diabetes (T2D) share common etiologic pathways that may long precede the development of clinically evident disease. Early identification of risk markers could support efforts to individualize risk prediction and improve the efficacy of primary prevention, as well as uncover novel therapeutic targets. Recent findings: Altered metabolism of branched-chain amino acids (BCAAs), and their subsequent accumulation in circulation, may precede the development of insulin resistance and clinically manifest cardiometabolic diseases. BCAAs – the essential amino acids leucine, isoleucine and valine – likely promote insulin resistance through activation of mammalian target of rapamycin complex 1. Epidemiologic studies demonstrate robust associations between BCAAs and incident T2D, and Mendelian randomization supports a potentially causal relationship. More recently, there is emerging evidence that BCAAs are also associated with incident atherosclerotic CVD, possibly mediated by the development of T2D. Summary: In this article, we review the biochemistry of BCAAs, their potential contribution to cardiometabolic risk, the available evidence from molecular epidemiologic studies to date, and, finally, consider future research and clinical directions. Overall, BCAAs represent a promising emerging target for risk stratification and possible intervention, to support efforts to mitigate the burden of cardiometabolic disease in the population.